TRANSFORMING RELIGIOUS LEARNING: EMPOWERING FAITH THROUGH VIRTUAL CONGREGATION IN INDONESIA - Alam, Lukis; Iqbal, Muh. (Hunafa: Jurnal Studia Islamika, 2024)
This paper examines the impact of digital Pesantren in Indonesia, addressing how they are shaping religious Islamic education in Indonesia. With the digital technology, Islamic education have encountered new modes of dissemination and engagement.Through a comprehensive review of literature and case studies, this study analyzes the proliferation of digital Pesantren, their methods of instruction, and their influence on practice among Indonesian Muslims. Findings this paper, digital Pesantren offer unprecedented accessibility, flexibility, and inclusivity. Furthermore, in digital Pesantren audiences can foster solidarity and mutually empower each other to deepen their faith, transcending geographical limitations.